2019
DOI: 10.1002/eji.201848022
|View full text |Cite
|
Sign up to set email alerts
|

Epithelium‐specific MyD88 signaling, but not DCs or macrophages, control acute intestinal infection with Clostridium difficile

Abstract: Infection with Clostridium difficile is one of the major causes of health care acquired diarrhea and colitis. Signaling though MyD88 downstream of TLRs is critical for initiating the early protective host response in mouse models of C. difficile infection (CDI). In the intestine, MyD88 is expressed in various tissues and cell types, such as the intestinal epithelium and mononuclear phagocytes (MNP), including DC or macrophages. Using a genetic gain‐of‐function system, we demonstrate here that restricting funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…There is an increased appreciation that different types of epithelial cells provide signals that help to coordinate the enteric nervous system, gut physiology and mucosal immunity in order to maintain tolerance. For extracellular pathogens, enterocytes promote clearance of the helminth Trichuris muris ( 74 ) and the bacteria Clostridium difficile ( 75 ) and Citrobacter rodentium ( 57 ). Less is known about how enterocytes respond to intracellular infections, although inflammasome-mediated extrusion of Salmonella -infected enterocytes limits bacterial spread ( 76 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is an increased appreciation that different types of epithelial cells provide signals that help to coordinate the enteric nervous system, gut physiology and mucosal immunity in order to maintain tolerance. For extracellular pathogens, enterocytes promote clearance of the helminth Trichuris muris ( 74 ) and the bacteria Clostridium difficile ( 75 ) and Citrobacter rodentium ( 57 ). Less is known about how enterocytes respond to intracellular infections, although inflammasome-mediated extrusion of Salmonella -infected enterocytes limits bacterial spread ( 76 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, this raises the question as to why animals infected with FM2.5, that show high and equivalent levels of tissue colonisation by 48 hpi and which are producing high amounts of toxin, do not show equivalent levels of weight loss and tissue inflammation at this and subsequent time points. Several studies have shown that the S-layer is essential in immune activation [ 39 , 40 ] driving the production of proinflammatory cytokines via TLR4/MyD88 dependent pathways and enhancing the toxin-activated inflammasome [ 32 , 41 , 42 ]. Together, this implies that the timing or spatial localisation of toxins and the S-layer relative to the epithelial barrier could be crucial to immune activation.…”
Section: Discussionmentioning
confidence: 99%
“…However, this raises the question as to why animals infected with FM2.5, that show high and equivalent levels of tissue colonisation by 48 hpi, do not show equivalent levels of weight loss and tissue inflammation as R20291 infected animals. Several studies have shown that the S-layer is essential in immune activation (Jarchum et al 2012; Mamareli et al 2019), driving the production of proinflammatory cytokines via TLR4/MyD88 dependent pathways and enhancing the toxin-activated inflammasome (Ryan et al, 2011; Cowardin et al, 2015; McDermott et al, 2016). Together, this implies that the timing or spatial localisation of toxins and the S-layer relative to the epithelial barrier could be crucial to immune activation.…”
Section: Discussionmentioning
confidence: 99%